Late-stage myeloma invades kidney without significant effect on renal function: findings from 53 autopsies in a single institute - Takano, Junichiro; Mine, Sohtaro; Mochizuki, Makoto; Tanaka, Noriko; Hagiwara, Shotaro (International Journal of Hematology, 2019)
Renal manifestations of multiple myeloma (MM) including cast nephropathy, amyloidosis, and renal calcification have been widely recognized. However, the severity of histopathological findings has not been addressed so far, and the clinical significance of these pathological findings is unclear. We sought to clarify the relationship between the severity of renal pathology and clinical characteristics. We analyzed 53 autopsies performed on patients who died from MM. The kidneys were evaluated using light microscopy, and the severity of pathological findings was recorded. The most common renal lesion was cast nephropathy ( n = 27). Other findings included amyloidosis ( n = 10), renal calcification ( n = 5), microbial infection ( n = 4), and MM infiltration ( n = 17). The incidence of MM infiltration was substantially higher than previously reported. Renal MM infiltration was detected even when bone marrow plasmacytosis was limited. However, a significantly higher degree of renal MM infiltration was observed when MM cells invaded the liver. No correlation was observed between serum creatinine levels and degree of MM infiltration, but these tended to be elevated when cast nephropathy was severe. These findings may provide clues to understand both renal injury and extramedullary diseases in patients with MM.